Insights into microbial contamination in multi-type manure-amended soils: The profile of human bacterial pathogens, virulence factor genes and antibiotic resistance genes - Zhu, Lin; Lian, Yulu; Lin, Da; Huang, Dan; Yao, Yanlai; Ju, Feng; Wang, Meizhen (Journal of hazardous materials, 2022)
Concerns regarding biological risk in environment have garnered increasing attention. Manure has been believed to be a significant source of antibiotic resistance genes (ARGs) in agricultural soil. Nevertheless, the profile of microbial contamination including ARGs, virulence factor genes (VFGs) and human bacterial pathogens (HBPs) in different manure-amended soils remain largely unknown. Here, we conducted the systematic metagenome-based study to explore changes in resistome, VFGs and HBPs in soils treated by frequently-used manures. The results revealed that many manure-borne ARGs, VFGs, and HBPs could be spreaded into soils, and their diversity and abundance were significantly different among chemical fertilizer, pig manure, chicken manure, cow dung and silkworm excrement application. A total of 157 potential HBPs accounting about 1.33% of total bacteria were detected. The main ARGs transferred from manures to soil conferred resistance to vancomycin and macrolide-lincosamide-streptogramin. The series analysis revealed positive co-occurrence patterns of ARGs-HBPs, VFGs-HBPs and ARGs-VFGs. Microbial contamination were more serious in pig manure and silkworm excrement sample than in the other samples, implying the usage of these two manures increased the risk of HBPs and dissemination of ARGs. This study confirmed the prevalence and discrepancy of resistome, VFGs and HBPs in different manure-amended soils. [Display omitted] •A total of 157 potential human bacterial pathogens were detected, accounting about 1.33% of total bacteria screened.•Abundant and diverse virulence factor genes and antibiotic resistance genes were identified in the agricultural soils.•The coexistence of many antibiotic resistance genes and virulence factor genes was found in human bacterial pathogens.•Pig manure and silkworm excrement increased higher microbiological risks in farmland soil.